Sosialisasi Pembuatan Teh Bunga Telang (Clitoria Ternatea L.) Sebagai Minuman Kesehatan Bagi Masyarakat Di Desa Sumber Jaya - Akmal Hawari; Wulan Puti Maulina Irwan; Utami Permata Andi Islami; Alika Nurmala Siregar; Nana Monica Sari; Ahmad Falah Elma; Azzahra Adeela Putri; Siti Khadijah Sabila; Rizka Aprilliana Utami; Desi Rahmadani Siagian (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Butterfly pea flower (Clitoria ternatea L.) is a plant that contains anthocyanins and bioflavonoids. This plant is able to increase antioxidant levels, as an anti-diabetic, thinning phlegm and reducing sugar, insulin levels and various other properties. Some villagers have butterfly pea plants in their yards, but don't know that these plants can be used as a health drink. This community service activity aims to educate the public about the properties/benefits of telang flowers which can be used as a health drink. Apart from that, it can be a commercial product that can be marketed widely so that it can become a source of income for the Sumber Jaya village community.